2009
DOI: 10.1128/aem.00266-09
|View full text |Cite
|
Sign up to set email alerts
|

Serogroup, Virulence, and Genetic Traits of Vibrio parahaemolyticus in the Estuarine Ecosystem of Bangladesh

Abstract: Forty-two strains of Vibrio parahaemolyticus were isolated from Bay of Bengal estuaries and, with two clinical strains, analyzed for virulence, phenotypic, and molecular traits. Serological analysis indicated O8, O3, O1, and K21 to be the major O and K serogroups, respectively, and O8:K21, O1:KUT, and O3:KUT to be predominant. The K antigen(s) was untypeable, and pandemic serogroup O3:K6 was not detected. The presence of genes toxR and tlh were confirmed by PCR in all but two strains, which also lacked toxR. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 38 publications
5
30
1
Order By: Relevance
“…In the subsequent years, several other serovars were genetically grouped with O3:K6 [27], [40]. In this study, we found that pandemic serovars such as O3:K6, O1:K25, O4:K68 and O1:KUT were clustered in one clade and several new serovars remained in the other.…”
Section: Discussionmentioning
confidence: 49%
“…In the subsequent years, several other serovars were genetically grouped with O3:K6 [27], [40]. In this study, we found that pandemic serovars such as O3:K6, O1:K25, O4:K68 and O1:KUT were clustered in one clade and several new serovars remained in the other.…”
Section: Discussionmentioning
confidence: 49%
“…Most of the environmental samples are selectively enriched first with alkaline peptone water (APW) and then plated on standard culture media for growth [17,18]. APW is the preferred enrichment medium for vibrios including V. parahaemolyticus.…”
Section: Introductionmentioning
confidence: 99%
“…parahaemolyticus [17,18,20]. The existing APW method has also been applied to detect V. parahaemolyticus in fresh water [20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that these serotypes probably originated from the same clone as O3:K6 (8,15,36). On the other hand, non-O3:K6 serovars with pandemic traits are increasingly isolated worldwide, and therefore, they may possibly have pandemic potential (2).…”
mentioning
confidence: 99%